URBAN LEFT-OVER SPACE: CHARACTERISTIC IDENTIFICATION OF THE IN-BETWEEN SPACES IN RIVERSIDE SETTLEMENT (CASE STUDY: MARTAPURA RIVERSIDE SETTLEMENT AT SASIRANGAN VILLAGE) - Juleta Nadea Anilaputri; Syam Rachma Marcillia (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2023)
The identity of